Palaeomagnetism of the 1.89?Ga Boonadgin dykes of the Yilgarn Craton: Possible connection with India - Liu, Yebo; Li, Zheng-Xiang; Pisarevskiy, Sergei; Kirscher, Uwe; Mitchell, Ross; Stark, J. Camilla (Elsevier BV, 2018)
A palaeomagnetic study was carried out on the newly identified 1888 ± 9 Ma Boonadgin dyke swarm of the Yilgarn Craton in Western Australia. The Bonnadgin dykes yield a mean direction of magnetisation of D = 143°, I = 13°, k = 37 and a 95 = 8°, based on samples from 10 diabase dykes, with a corresponding palaeopole at 47° S, 235° E, A 95 = 6°. A positive baked contact test establishes the primary nature of the magnetisation. The ca. 1.89 Ga palaeopole suggests that the Yilgarn Craton was near the equator at this time, and the Boonadgin dyke swarm can be interpreted to represent an arm of a radiating dyke swarm that shared the same plume centre with coeval mafic dykes in the Dharwar and Bastar cratons of southern India. We therefore propose that the West Australian Craton (WAC, consisting of the Yilgarn and Pilbara cratons) and the South Indian Block (SIB, consisting of the Dharwar, Bastar, and Singhbhum cratons) were connected ca. 1.89 Ga. Globally, available high-quality palaeopoles of similar age allow the West Australian Craton to be placed northwest of proto-Laurentia during the assembly of the supercontinent Nuna.